Ecology, cytology and phylogeny of the snow alga Scotiella cryophila K-1 (Chlamydomonadales, Chlorophyta) from the Austrian Alps - Remias, Daniel; Procházková, Lenka; Holzinger, Andreas; Nedbalová, Linda (Phycologia, 2018)
Long-lasting, slowly melting snowfields in mountainous regions are frequently populated by specialised microalgae whose diversity is still vastly underestimated. Cysts causing sub-surficial green snow were collected in the Austrian Alps, Tyrol, and morphologically accorded to the snow alga Scotiella cryophila sensu Chodat, initially described from Switzerland. The cytology and photobiology of this population were investigated to understand mechanisms of adaptation to the harsh habitat. Cysts of S. cryophila K-1 had secondary cell walls with pronounced rib-like surface structures and contained several small spherical plastids. The cytoplasm was dominated by lipid bodies, which developed reddish secondary pigmentation. Partial life cycle observations showed that daughter cells lacked structured cell walls. Cysts performed active photosynthesis at temperature conditions close to the freezing point and were photoinhibited at irradiances greater than 70 μmol m-2 s-1. This corresponded exactly to habitat conditions 20 to 40 cm below the snow surface. Phylogenetic analyses using 18S rDNA, rbcL and ITS2 rDNA sequences indicated that S. cryophila K-1 is related to Chloromonas, known to contain several snow algae. The taxon forms an independent lineage and is clearly genetically distinct from the type strain of Chloromonas rosae var. psychrophila from North America that is supposed to have morphologically identical cysts. For a taxonomic treatment including a species assignment of S. cryophila K-1 from Europe within Chloromonas, flagellates will have to be cultivated from cysts or from acquired field material for a detailed morphological description. Acquisition and genetic analysis of cysts that resemble S. cryophila from America could elucidate their relationship to European samples.
Keywords: Cysts; Fluorometry; Cryospheric algae; Cryoflora; Extremophiles; Ultrastructure